The rhetorical organization and identity of Japanese editorial writers - Keizo Nanri (Ilha do Desterro)
The present paper has two purposes. The first is to demonstrate how homogeneous and innocuous editorials in Japanese major newspapers are. Specifically, I will first show that editorials whose political stance is anti-US/anti-government or neutral with respect to the US and Japanese governments’ decisions, frequently employ the rhetorical structure1 which leaves responsibility for solving critical issues to a large political system, and that this rhetorical structure prevents the text from providing the issues with specific and implementable solutions. I will then point out that, regardless of their political stance, Japanese editorials have a strong tendency to comment on events under discussion by raising the same issues at the same time within the framework of the central government’s policies. The second purpose is to argue that the elimination of editorial homogeneity and innocuousness requires the abolition of the kisha (press) club system.